The pathogen Pseudomonas aeruginosa optimizes the production of the siderophore pyochelin upon environmental challenges. Issue 12 (8th December 2020) - Cunrath, Olivier; Graulier, Gwenaëlle; Carballido-Lopez, Ana; Pérard, Julien; Forster, Anne; Geoffroy, Valérie A.; Saint Auguste, Pamela; Bumann, Dirk; Mislin, Gaetan L. A.; Michaud-Soret, Isabelle; Schalk, Isabelle J.; Fechter, Pierre
Abstract : Representation of the regulation of pyochelin production, a siderophore produced by the pathogen Pseudomonas aeruginosa to access iron. This regulation involves a positive auto-regulation loop. Abstract : Siderophores are iron chelators produced by bacteria to access iron, an essential nutrient. The pathogen Pseudomonas aeruginosa produces two siderophores, pyoverdine and pyochelin, the former with a high affinity for iron and the latter with a lower affinity. Furthermore, the production of both siderophores involves a positive auto-regulatory loop: the presence of the ferri-siderophore complex is essential for their large production. Since pyochelin has a lower affinity for iron it was hard to consider the role of pyochelin in drastic competitive environments where the host or the environmental microbiota produce strong iron chelators and may inhibit iron chelation by pyochelin. We showed here that the pyochelin pathway overcomes this difficulty through a more complex regulating mechanism for pyochelin production than previously described. Indeed, in the absence of pyoverdine, and thus higher difficulty to access iron, the bacteria are able to produce pyochelin independently of the presence of ferri-pyochelin. The regulation of the pyochelin pathway appeared to be more complex than expected with a more intricate tuning between repression and activation. Consequently, when the bacteria cannot produce pyoverdine they are able to produce pyochelin even in the presence of strong iron chelators. Such results support a more complex and varied role for this siderophore than previously described, and complexify the battle for iron during P. aeruginosa infection.